Clinical characteristics of COVID-19 patients with HIV coinfection in Wuhan, China. (4th March 2021) - Yang, Rongrong; Gui, Xien; Zhang, Yongxi; Xiong, Yong; Gao, Shicheng; Ke, Hengning
ABSTRACT: Background: Information about the impact of HIV coinfection on clinical characteristics of COVID-19 patients remains limited. Methods: Maximum body temperatures, fever duration, chest CT and viral shedding, lymphocyte counts, and titer of SARS-CoV-2 antibody were compared between COVID-19 patients with and without HIV infection in Zhongnan Hospital of Wuhan University from January 20th to February 14th, 2020. Results: Compared with 53 COVID-19 patients without HIV infection, the patients with SARS-CoV-2 and HIV coinfection had higher maximum body temperatures (38.7°C vs 37.6°C, P = 0.044), longer duration of fever (8.7 ± 4.5 vs 4.2 ± 2.1 days, P = 0.038), longer time to have improvement of chest CT images (22 vs 15 days from the onset of illness, P = 0.011), lower level of SARS-CoV-2 IgG (5.11 ± 32.33 vs 37.45 ± 15.48 AU/ml, P = 0.042). However, no statistically significant difference of duration of SARS-CoV-2 shedding in the two groups was found (12.3 ± 2.6 vs 13.4 ± 2.4 days, , P = 0.813). Conclusion: Lower level of CD4 + T lymphocyte counts caused by HIV infection itself might be one of reasons for relatively weak ability to produce SARS-CoV-2 specific antibodies. The effects of anti-HIV drugs in prevention and treatment of COVID-19 appears to be limited.